Peningkatan Hasil Belajar Peserta Didik melalui Implementasi Metode Inquiry - Pebri, Rahmatul; Elfizon, Elfizon (Jurnal Pendidikan Teknik Elektro, 2024)
This study aims to determine the improvement of student learning outcomes through the inquiry method at SMK Negeri 1 Sutera. The results of observations in class, understanding of the concepts taught is minimal, and critical thinking skills are weak. This study uses quantitative and experimental research types using the Pre-Experiment method with the One Group Pretest Posttest Design type. This study uses a test in the form of a pretest which aims to measure the level of students' initial understanding before being given treatment, and a posttest which seeks to assess the level of students' knowledge after treatment. Both are in the form of objective questions. The study subjects consisted of class X TITL 2 students of SMK Negeri 1 Sutera: The data collection method included observation, pretest, posttest, and documentation. Before the instrument was used in the experimental group, a trial of validity, reliability, and discrimination power, as well as the level of difficulty of the questions was carried out to ensure the suitability of the instrument with the research objectives. The result of his study in dictation increased student learning outcomes through the calculation of the Normalized Gain Score with a moderate and quite effective category.